2012
DOI: 10.4103/1658-354x.105878
|View full text |Cite
|
Sign up to set email alerts
|

Premedication for neonatal intubation: Current practice in Saudi Arabia

Abstract: Background:Despite strong evidence of the benefits of rapid sequence intubation in neonates, it is still infrequently utilized in neonatal intensive care units (NICU), contributing to avoidable pain and secondary procedure-related physiological disturbances.Objectives:The primary objective of this cross-sectional survey was to assess the practice of premedication and regimens commonly used before elective endotracheal intubation in NICUs in Saudi Arabia. The secondary aim was to explore neonatal physicians’ at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…A prospective study of 13 tertiary care units in Paris, France published in 2013 showed that using premedication before intubation was either inconsistent or it did not follow current recommendations (7). Similar results were reported in a Saudi Arabian study published in 2012 (8).…”
Section: Introductionmentioning
confidence: 56%
“…A prospective study of 13 tertiary care units in Paris, France published in 2013 showed that using premedication before intubation was either inconsistent or it did not follow current recommendations (7). Similar results were reported in a Saudi Arabian study published in 2012 (8).…”
Section: Introductionmentioning
confidence: 56%
“…4,10 Há evidências de que a intubação orotraqueal sem analgesia em neonatos pode levar a complicações hemodinâmicas como hipoxemia, bradicardia, hipertensão intracraniana e hemorragia periintraventricular. 18,19 Nas unidades de terapia intensiva neonatais, o uso de analgesia e sedação é eventual, desconsiderando-se a dor e o desconforto do paciente, que ainda não apresenta condições verbais de expor o que sente. Apesar dos avanços no conhecimento da fisiologia da dor nessa faixa etária, do desenvolvimento de métodos de avaliação da dor para o lactente pré-verbal e da existência de medidas terapêuticas para o alívio da dor, ainda há uma grande lacuna entre o conhecimento teórico e a conduta prática por parte dos profissionais de saúde.…”
Section: Resultsunclassified
“…One of the reasons identified from the literature 29,30 for variations in the frequency of premedication is the concern with adverse effects of the drugs. The AAP clinical report attempts to address this concern by listing the available drugs used with their adverse effects and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%